Potentiometric Determination of the Formation Constants of Complexes of 3,3´ ,4´ ´ -Triaminodipropylbutylamine with Co(II), Ni(II), Cu(II) and Zn(II) - Keypour, Hassan; Kianfar, Farahnaz (Asian Journal of Chemistry, 2010)
The tripodal 3,3,4-tetraamine ligand N{CH2)3NH2}2(CH2)4NH2 (L = ppb) has been investigated for the first time as asymmetrical tetraamine chelating agent for cobalt(II), nickel(II), copper(II) and zinc(II). The protonation constants of ppb and formation constants of ppb and formation constants of its complexes have been determined potentiometrically in 0.1 M KCl at 25ºC. The successive protonatoin constants (log Kn) are: 10.69, 10.12,9.49,6.72 (n = 1–4). Two complexes having the formulae ML, MHL (where L = ppb) are common to all the four metal ions for which the formation constants {log βML, M = Co2+, Ni2+ Cu2+, Zn2+) are: 6.70, 6.79,12.98 and 9.37 and {log βMHL, M= Co2+, Ni2+, Cu2+, Zn2+) are: 14.94, 16.09,22.20 and 17.24 respectively. In addition to the simple and protonated complexes, cobalt(II), copper(II) and zinc(II) give the hydroxo complexes and nickel(II) gives the ML2 complexes. The nickel(II) complex, Ni(ppb )·(ClO4)2·1.5H2O and zinc(II) complex, Zn(ppb)·(ClO4)·H2O, have been isolated.